The Influence of Entrepreneurial Knowledge and Entrepreneurial Skills on Business Success - Fauziah, Anjani; Hamdani, Nizar Alam; Nugraha, Sukma (Entrepreneurship Faculty, Universitas Garut, 2024)
Garut Regency is a city that offers great opportunities to start a business, especially in the culinary sector. The increasing number of culinary businesses that local residents in Garut are interested in. Because their enthusiasm for culinary tourism is quite large, it creates tempting opportunities for entrepreneurs who want to plan to open a business in this sector. This research was conducted at Kerkof Culinary Tourism which is located on Jl. Merdeka Tarogong Kidul District. The aim of this research is to test a hypothesis that explains the relationship between the variables of entrepreneurial knowledge and entrepreneurial skills on business success in the Kerkof Culinary Tourism, Garut Regency. The reason for carrying out this research is to understand how these factors are interconnected and contribute to the success of Kerkof Culinary Tourism Micro, Small and Medium Enterprises (MSMEs). The research method used was a quantitative method with a descriptive approach, primary data was obtained through distributing questionnaires to 47 respondents who were actors in the Kerkof Culinary Tourism Micro, Small and Medium Enterprises (MSMEs) using a saturated sampling technique. The data analysis technique uses Partial Least Square-Structural Equation Modeling with the help of SmartPLS 4.0 software. The research results show that entrepreneurial knowledge has a positive and significant effect on business success and entrepreneurial skills have a positive and significant effect on business success.